(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Seasonal variation significantly impacts groundwater quality, but its effects can vary depending on hydrogeological settings. This study investigates the comparative impact of seasonal variation on groundwater quality in different hydrogeological settings in Akaba-Atissa community. Water samples were collected from 3 boreholes in three different locations with difference hydrogeological settings during dry, moderately wet and wet seasons. Physicochemical and Heavy/Light Metals parameters were analyzed and results compared with WHO guidelines, comparative study were done with observed results within locations and seasons and then validated using analysis of variances. The results showed that location B exceeded WHO guidelines for sulphate (4.36-4.40 mg/L) and total hydrocarbon (114-116 mg/L), while location C showed high nitrate levels (0.272-0.274 mg/L) but location A maintained relatively stable and low contaminant levels. The ANOVA analysis indicate significant differences in groundwater quality between locations at (p < 0.001) while Seasonal variations are insignificant for most parameters at (p > 0.05) with strong correlations exist between parameters at R-values ranging from0.7-0.96. The significant F-values (p < 0.001) for "Between Locations" indicate that there are significant differences in groundwater quality between Location A, B, and C. The non-significant F-values (p = 0.471) for "Between Seasons" suggest that seasonal variations are not significant for most parameters. The non-significant F-values (p = 0.627) for "Interaction" indicate that the interaction between locations and seasons is not significant. The study had identified the significant water quality variations across locations with no significant differences due to seasonal variations but due to hydrogeological setting.